A Variable Structure Control Algorithm for Robot Manipulators Using Acceleration Feedback - Machado, J. A. Tenreiro (1990)
A new variable structure control algorithm for robot manipulators is announced. Second order linear system sliding curves and a new control law, eliminate the reaching phase problems as well as the chattering usually present in the sliding mode. This controller architecture may also be interpreted as the result of the acceleration data integration on the VSS algorithm. Consequently, there is a shift from the computational burden, often present in sophisticated control schemes, towards a simpler but highly sensor based structure. The results show a remarkable improvement over conventional VSS controllers, maintaining, however, a low computational complexity which make it well suited for microcomputer implementation.